Textile characteristics of Huacaya alpaca fibre in high Andean communities of the Tacna region, Peru - Gandarillas Espezua, Daniel (2022)
The study was carried out in two communities of the Tacna Region, Peru to determine textile characteristics of Huacaya alpaca fibre and its degree of association with sex, age and coat colour. Fibre samples from 817 and 683 alpacas from the Huaytire and Maure communities, respectively, were analysed with the OFDA 2000 equipment. The experimental design corresponded to a complete random block 2x5x2 with fixed effects. The alpaca fibre of the Huaytire community presented finer fibres (20.51±2.52 µm) and less dispersion (5.15±0.96 µm), with greater comfort (93.85±8.26%) and a higher curvature index (36.58±5.79 °/mm), as well as longer wick length (10.45±2.21 cm). The white fibres have greater fineness (20.79±2.62 µm), and less dispersion (5.18±0.95 µm) than the coloured ones, while the comfort factor, curvature index and wick length of the white fibres showed greater values. In relation to the age group, the young alpacas presented better textile characteristics than the adults, while only fineness showed significant differences (p<0.05) in favour of the male. The wick length showed no association with the other textile characteristics. In conclusion, the textile characteristics vary according to the community, sex, age and coat colour, where the best results were found in the Huaytire community, in males, in white fibres and in young animals.